UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN MELALUI MEDIA PAPAN LABIRIN KELAS 3 SEKOLAH DASAR TAHUN AJARAN 2024/2025 - Aulia Azizah; Nadia Deviyana; Yunika Nur Indah Sari; Choirun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low learning outcomes of students in learning mathematics, especially in addition and subtraction materials with the method of saving and borrowing. This study aims to improve the learning outcomes of 3rd grade students of SD Muhammadiyah 1 Surakarta on the material of addition and subtraction using the maze board media. This research is a qualitative research with a class action research design (PTK) and the research subjects are 3rd grade students of SD Muhammadiyah 1 Surakarta. This research was conducted in two cycles. Data collection techniques in this study used tests, observation and documentation. The data obtained were analyzed using qualitative descriptive analysis. The results showed that the learning outcomes of students increased significantly after using the labyrinth board learning media during the learning process.